USING â€œUNFINISHED STORYâ€ TO IMPROVE STUDENTSâ€™ WRITING ABILITY OF THE FIRST GRADE OF ENGLISH EDUCATION PROGRAM OF STKIP HAMZANWADI SELONG - Laila Wati (Educatio, 2012)
This research was designed to improve the studentsâ€™ writing narrative text in English through unfinished story.  A collaborative action research design was employed, involving the researcher and a collaborator.The design applied in this research was a classroom action research. Data in the form of observation checklist and studentsâ€™ writing product were collected at the end of the cycle then analysed qualitatively and quantitatively. The success was determined from the improvement of the studentsâ€™ score on their writing product. The findings respectively showed that the unfinished story improved the studentsâ€™ writing ability. The improvement can be seen on the studentsâ€™ individual writing scores. The findings also showed that this media was effective in enhancing the studentsâ€™ involvement in the instructional activities. Key words: unfinished story, narrative text, writing ability